2007
DOI: 10.1121/1.2783124
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian representation of high-intensity focused ultrasound beams

Abstract: A method for fast numerical simulation of high-intensity focused ultrasound beams is derived. The method is based on the frequency-domain representation of the Khokhlov-Zabolotskaya-Kuznetsov (KZK) equation, and assumes for each harmonic a Gaussian transverse pressure distribution at all distances from the transducer face. The beamwidths of the harmonics are constrained to vary inversely with the square root of the harmonic number, and as such this method may be viewed as an extension of a quasilinear approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…Simplifying assumptions have been needed in the past for modeling beam patterns from ultrasound transducers, as one-way parabolic approximations, most based on the Khokhlov-ZabolotskayaKuznetsov equation (KZK) [1][2][3][4][5][6][7][8] . To overcome the validity limitations of the parabolic approximations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Simplifying assumptions have been needed in the past for modeling beam patterns from ultrasound transducers, as one-way parabolic approximations, most based on the Khokhlov-ZabolotskayaKuznetsov equation (KZK) [1][2][3][4][5][6][7][8] . To overcome the validity limitations of the parabolic approximations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature vs. time history was obtained by solving the bio-heat equation proposed by Pennes (1948) numerically [29]. The explicit form of this equation is given by:…”
Section: Simulation Modelmentioning
confidence: 99%
“…The power field was estimated using the KZK model [20]. The temperature vs time history was obtained by solving the bio-heat equation proposed by Pennes numerically [22].…”
Section: Simulation Modelmentioning
confidence: 99%
“…Recently, experiments have demonstrated the ability of HIFU used for noninvasive procedures to dissolve thrombus [2, 3,[18][19][20]. Maxwell et al reported that histotripsy therapy using short, HIFU pulses can cause mechanical breakdown of targeted soft tissue by acoustic cavitation, which is guided by real-time ultrasound imaging [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation